2004
DOI: 10.1093/humrep/deh074
|View full text |Cite
|
Sign up to set email alerts
|

Differential FSH exposure in preantral follicle culture has marked effects on folliculogenesis and oocyte developmental competence

Abstract: Exposure to FSH before formation of the antral-like cavity had a positive effect on follicle survival and oocyte robustness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
110
1
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(123 citation statements)
references
References 31 publications
6
110
1
5
Order By: Relevance
“…The elevations in caspase-3 and caspase-7 activities in thecainterstitial cells were accompanied by an increase in apoptosis [50]. Furthermore, Adriaens et al [51] have shown that differential FSH exposure in preantral follicle culture has marked effects on folliculogenesis and oocyte developmental competence. Although early preantral follicles are independent of FSH for their initial growth, FSH receptors are present on the GCs of these follicles [51].…”
Section: I: Interruption Of Follicle-stimulating Hormone Secretionmentioning
confidence: 99%
See 3 more Smart Citations
“…The elevations in caspase-3 and caspase-7 activities in thecainterstitial cells were accompanied by an increase in apoptosis [50]. Furthermore, Adriaens et al [51] have shown that differential FSH exposure in preantral follicle culture has marked effects on folliculogenesis and oocyte developmental competence. Although early preantral follicles are independent of FSH for their initial growth, FSH receptors are present on the GCs of these follicles [51].…”
Section: I: Interruption Of Follicle-stimulating Hormone Secretionmentioning
confidence: 99%
“…Furthermore, Adriaens et al [51] have shown that differential FSH exposure in preantral follicle culture has marked effects on folliculogenesis and oocyte developmental competence. Although early preantral follicles are independent of FSH for their initial growth, FSH receptors are present on the GCs of these follicles [51]. The best known FSH receptor is FSHR-1 [51].…”
Section: I: Interruption Of Follicle-stimulating Hormone Secretionmentioning
confidence: 99%
See 2 more Smart Citations
“…The capacity of the cumulus to support oocyte maturation during antral follicle growth requires two types of stimulation: stimulation of oocyte factors GDF9 and BMP15 (Lucidi et al 2003, Pangas & Matzuk 2005, and gonadotropin stimulation with FSH and/or LH (Adriaens et al 2004, Sirard et al 2007. Additionally, gonadotropin signal transduction by the somatic compartment requires de novo mRNA synthesis within CCs (Meinecke & Meinecke-Tillmann 1993).…”
Section: Introductionmentioning
confidence: 99%